Exploratory Study of Apparent Diffusion Coefficient Histogram Metrics in Assessing Pancreatic Malignancy. Issue 4 (November 2019) - Taffel, Myles T.; Luk, Lyndon; Ream, Justin M.; Rosenkrantz, Andrew B.
Purpose: To evaluate whole-lesion 3D-histogram apparent diffusion coefficient (ADC) metrics for assessment of pancreatic malignancy. Methods: Forty-two pancreatic malignancies (36 pancreatic adenocarcinoma [PDAC], 6 pancreatic neuroendocrine [PanNET]) underwent abdominal magnetic resonance imaging (MRI) with diffusion-weighted imaging before endoscopic ultrasound biopsy or surgical resection. Two radiologists independently placed 3D volumes of interest to derive whole-lesion histogram ADC metrics. Mann-Whitney tests and receiver operating characteristic analyses were used to assess metrics' diagnostic performance for lesion histology, T-stage, N-stage, and grade. Results: Whole-lesion ADC histogram metrics lower in PDACs than PanNETs for both readers ( P ≤ .026) were mean ADC (area under the curve [AUC] = 0.787-0.792), mean of the bottom 10th percentile (mean0-10 ) (AUC = 0.787-0.880), mean of the 10th-25th percentile (mean10-25 ) (AUC = 0.884-0.917) and mean of the 25th-50th percentile (mean25-50 ) (AUC = 0.829-0.829). For mean10-25 (metric with highest AUC for identifying PDAC), for reader 1 a threshold > 0.94 × 10 −3 mm 2 /s achieved sensitivity 94% and specificity 83%, and for reader 2 a threshold > 0.82 achieved sensitivity 97% and specificity 67%. Metrics lower in nodal status ≥ N1 than N0 for both readers ( P ≤ .043) were mean0-10 (AUC = 0.789-0.822) and mean10-25 (AUC = 0.800-0.822). For mean10-25 (metric with highest AUC for identifying N0 ), for reader 1 a threshold <1.17 achieved sensitivity 87% and specificity 67%, and for reader 2 a threshold <1.04 achieved sensitivity 87% and specificity 83%. No metric was associated with T-stage ( P > .195) or grade ( P > .215). Conclusion: Volumetric ADC histogram metrics may serve as non-invasive biomarkers of pancreatic malignancy. Mean10-25 outperformed standard mean for lesion histology and nodal status, supporting the role of histogram analysis.